Peningkatan Pengetahuan Mengenai Infeksi Menular Seksual Melalui Metode Penyuluhan pada Kelompok Palang Merah Remaja SMAN 1 Kediri Tabanan - Indah Puspasari; Yukta Panditama; Gloria Puspawan Ni Putu Eka; Hendrika Vijayanti Ni Putu Dita (Warmadewa University Press, 2023)
Sexually Transmitted Infections (STI) is an infection caused by viruses, bacteria, parasites, protozoa and fungi that are transmitted primarily through sexual contact, including anal and oral. In additions, STIs can also be transmitted through direct contact with contaminated objects such as towels, sex toys, thermometers, syringes, and from infected mother to her baby before or during birth. Teenagers are more vulnerable to STIs while adolescents are more often encouraged to explore sexual experiences that if carried out without guidance and direction, can put them at risk of suffered STIs. SMAN 1 Kediri Tabanan has one of the youth activity at school, namely the Palang Merah Remaja (PMR) which is a forum for fostering and developing PMI youth members as a driving force for peer youth training in the field of adolescent health. This PKM activity aims to increase youth knowledge about STIs and be able to spread their knowledge to the surrounding environment. PKM activities begin with socialization, implementation, and evaluation of activity results. The expected outcome of this PKM is an increase in partners' knowledge about STIs, starting from the causes of the disease, types of disease, symptoms that arise in both men and women, ways of transmission and prevention. PKM activities results was found an increase in partners' knowledge about STIs by 80.84%.